Cooperative teams in initial teacher training: a study from the student's point of view (Praxis Educativa, 2023)
This study investigates the effectiveness and impact of cooperative dynamics and cooperative teams in the achievement of cooperative competences in initial teacher education. A total of 128 students took part. The study is based on a mixed methodology. The quantitative data were analysed using descriptive and inferential statistics and the qualitative information was analysed using content analysis. The results show that there are no statistically significant differences between the pre-test and the post-test globally, nor are there statistically significant differences between men and women. However, there are statistically significant differences between students from the upper secondary school and those from the baccalaureate. The results also provide information on the weaknesses, strengths, threats, and opportunities perceived by the cooperative teams and the improvements to be made for future teamwork.
Keywords: cooperative learning; cooperative skills; cohesion; inclusion; initial teacher training